Bridging versus direct endovascular therapy in basilar artery occlusion. Issue 9 (25th May 2021) - Nappini, Sergio; Arba, Francesco; Pracucci, Giovanni; Saia, Valentina; Caimano, Danilo; Limbucci, Nicola; Renieri, Leonardo; Zini, Andrea; Inzitari, Domenico; Toni, Danilo; Mangiafico, Salvatore
Abstract : Background: We evaluated safety and efficacy of intravenous recombinant tissue Plasminogen Activator plus endovascular (bridging) therapy compared with direct endovascular therapy in patients with ischaemic stroke due to basilar artery occlusion (BAO). Methods: From a national prospective registry of endovascular therapy in acute ischaemic stroke, we selected patients with BAO. We compared bridging and direct endovascular therapy evaluating vessel recanalisation, haemorrhagic transformation at 24–36 hours; procedural complications; and functional outcome at 3 months according to the modified Rankin Scale. We ran logistic and ordinal regression models adjusting for age, sex, National Institutes of Health Stroke Scale (NIHSS), onset-to-groin-puncture time. Results: We included 464 patients, mean(±SD) age 67.7 (±13.3) years, 279 (63%) males, median (IQR) NIHSS=18 (10–30); 166 (35%) received bridging and 298 (65%) direct endovascular therapy. Recanalisation rates and symptomatic intracerebral haemorrhage were similar in both groups (83% and 3%, respectively), whereas distal embolisation was more frequent in patients treated with direct endovascular therapy (9% vs 3%; p=0.009). In the whole population, there was no difference between bridging and direct endovascular therapy regarding functional outcome at 3 months (OR=0.79; 95% CI=0.55 to 1.13). However, in patients with onset-to-groin-puncture time ≤6 hours, bridging therapy was associated with lower mortality (OR=0.53; 95% CI=0.30 to 0.97) and a shift towards better functional outcome in ordinal analysis (OR=0.65; 95% CI=0.42 to 0.98). Conclusions: In ischaemic stroke due to BAO, when endovascular therapy is initiated within 6 hours from symptoms onset, bridging therapy resulted in lower mortality and better functional outcome compared with direct endovascular therapy.